Working hours and earnings: are mates’ answers coherent? - Pereira, Pedro Telhado (2012)
As surveys about time allocation among couples are extremely expensive, one way of reducing costs could be to query only one member of the coupler with the same set of questions about him/her and about his/her partner. In this paper we show that after carrying out a survey in this way, the responses given by one partner do not always fit the same econometric model as those obtained from the other.